Synthesis of high molecular weight sulfonated poly(arylene ether sulfone) copolymer without azeotropic reaction - Lee, So Young; Kwon, Yeonhye; Kim, Bo Hyun; Chae, Jieon; Jang, Jong Hyun; Henkensmeier, Dirk; Yoo, Sung Jong; Kim, Jin Young; Kim, Hyoung-Juhn (Elsevier BV, 2015)
Currently, most sulfonated poly(arylene ether sulfone) (s-PAES) polymers are synthesized using a solvent mixture consisting of toluene and dimethylacetamide (DMAc) by two successive reactions, namely azeotropic water removal, followed by nucleophilic substitution. In this study, a novel method for the synthesis of s-PAES polymers has been developed, where alcohols such as methanol, ethanol, or 2-propanol are used along with DMAc as the co-solvent in the place of toluene that is used in the conventional synthesis of s-PAES. Moreover, the synthesis method used in this study involves only one step, namely the polymerization at 160 degrees C and does not require the azeotropic water distillation step at 140 degrees C. The new synthesis method was found to yield s-PAES polymers with a higher molecular weight in a shorter reaction time compared to the conventional polymerization method. Further, membrane electrode assemblies (MEA) were fabricated using the synthesized s-PAES polymer membranes, in order to evaluate the performance of the membranes in polymer electrolyte membrane fuel cells (PEMFCs). The results indicate that the s-PAES membranes synthesized using the method proposed in this study have a great potential for use as PEMFC membranes. (C) 2015 Published by Elsevier B.V.